Envisioning the future of polymer therapeutics for brain disorders. (14th June 2018) - Rodriguez‐Otormin, Fernanda; Duro‐Castano, Aroa; Conejos‐Sánchez, Inmaculada; Vicent, María J.
Abstract : The growing incidence of brain‐related pathologies and the problems that undermine the development of efficient and effective treatments have prompted both researchers and the pharmaceutical industry to search for novel therapeutic alternatives. Polymer therapeutics (PT) display properties well suited to the treatment of neuro‐related disorders, which help to overcome the many hidden obstacles on the journey to the central nervous system (CNS). The inherent features of PT, derived from drug(s) conjugation, in parallel with the progress in synthesis and analytical methods, the increasing knowledge in molecular basis of diseases, and collected clinical data through the last four decades, have driven the translation from "bench to bedside" for various biomedical applications. However, since the approval of Gliadel® wafers, little progress has been made in the CNS field, even though brain targeting represents an ever‐growing challenge. A thorough assessment of the steps required for successful brain delivery via different administration routes and the consideration of the disease‐specific hallmarks are essential to progress in the field. Within this review, we hope to summarize the latest developments, successes, and failures and discuss considerations on designs and strategies for PT in the treatment of CNS disorders. This article is categorized under: Therapeutic Approaches and Drug Discovery > Nanomedicine for Neurological Disease Nanotechnology Approaches to Biology > Nanoscale Systems in Biology Therapeutic Approaches and Drug Discovery > Nanomedicine for Oncologic Disease Abstract : Polymer therapeutics represent promising novel chemical entities under development for addressing CNS disorders, in which intravenous and intranasal administration are the most appealing strategies to achieve this paramount goal.